Scratch-resistant stone plastic floor and preparation method thereof
Patent Information
- Application Number
- CN202510922886.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-04
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-07-04
AI Technical Summary
[0003]然而,现有的石塑地板在实际使用过程中仍存在一些亟待解决的问题
[0030] 1. Significantly improves wear resistance: By using polyvinyl chloride resin as the basic skeleton, combined with nano silica and polysiloxane scratch-resistant additives, a dense and low-friction coefficient protective layer is formed on the floor surface, effectively reducing the damage caused by daily friction and scratches to the floor and extending the service life of the floor.
Smart Images

Figure CN120739294B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of scratch-resistant layered products, specifically to a scratch-resistant stone-plastic flooring and its preparation method. Background Technology
[0002] With the continuous improvement of people's living standards and the development of the building decoration industry, the requirements for flooring materials are becoming increasingly stringent. Stone plastic flooring, as a new type of environmentally friendly flooring material, is favored by the market for its many advantages such as being lightweight, waterproof, fireproof, corrosion-resistant, and easy to clean, and is widely used in various scenarios such as residential and commercial spaces.
[0003] However, existing stone-plastic flooring still has some problems that urgently need to be solved in actual use. Traditional stone-plastic flooring has relatively poor wear resistance. Over long-term use, the surface is easily scratched by daily friction and abrasion, which not only affects the appearance of the flooring but may also reduce its lifespan. For example, in some high-traffic public places, such as shopping malls and schools, ordinary stone-plastic flooring may show obvious wear marks in a short period of time, requiring frequent replacement.
[0004] In addition, the materials used in the wear layer of some stone plastic flooring are insufficient in terms of UV resistance and weather resistance. Prolonged exposure to sunlight can easily lead to aging and fading, further affecting the flooring's performance and appearance. Furthermore, some stone plastic flooring designs are not well-designed, with insufficient bonding between layers, which may cause delamination and bulging during use, causing inconvenience to users and increasing maintenance costs.
[0005] Given the numerous problems with existing stone-plastic flooring, the market urgently needs a new type of stone-plastic flooring that can effectively solve these problems in order to meet people's demand for high-quality flooring. Summary of the Invention
[0006] The purpose of this invention is to address the problems existing in the prior art by providing a scratch-resistant stone plastic flooring with high wear resistance, UV resistance, and strong interlayer bonding.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is: a scratch-resistant stone plastic flooring, which consists of a three-layer structure stacked from top to bottom: a scratch-resistant transparent layer, a substrate layer, and a balancing layer;
[0008] The scratch-resistant transparent layer has a thickness of 0.05-0.3 mm, the substrate layer has a thickness of 1.5-5.0 mm, and the balancing layer has a thickness of 1.0-2.0 mm.
[0009] The scratch-resistant transparent layer is composed of a scratch-resistant transparent material, which contains the following components by weight: 80-95 parts polyvinyl chloride, 5-15 parts nano silica, 1-5 parts polysiloxane scratch-resistant additives, and 0.5-3 parts ultraviolet light absorber.
[0010] The ultraviolet light absorber is a compound represented by Formula 1:
[0011]
[0012] R1 is selected from: methyl, cyano, methyl cyano, acetic acid.
[0013] Furthermore, the particle size of the nano-silica is 10-50 nm.
[0014] Furthermore, the polysiloxane-based scratch-resistant additive is bis-3-methylpropenyloxypropyltetramethyldisiloxane.
[0015] Furthermore, the ultraviolet light absorber is any one of the compounds shown in the following structures:
[0016]
[0017] Furthermore, the preparation method of the scratch-resistant transparent material is as follows: the polyvinyl chloride resin, nano silica, polysiloxane scratch-resistant additive and ultraviolet light absorber are added to a mixer and mixed at 80-120°C for 5-15 minutes to obtain a mixture; the mixture is added to a twin-screw extruder and melt-extruded at 150-200°C, granulated, and cooled to room temperature to obtain the scratch-resistant transparent material.
[0018] Furthermore, the material of the substrate layer is polyvinyl chloride resin.
[0019] Furthermore, the material of the balancing layer is cork.
[0020] A method for preparing scratch-resistant stone-plastic flooring includes the following steps:
[0021] S1. Preparation of scratch-resistant transparent layer: A scratch-resistant transparent material is prepared according to the above method and then calendered into a film with a thickness of 0.05-0.3 mm;
[0022] S2. Preparation of substrate layer: Polyvinyl chloride resin is melted and plasticized at 160-190℃, and then calendered or extruded into a sheet with a thickness of 1.5-5.0mm;
[0023] S3. Preparation of the balancing layer: The cork raw material is hot-pressed at 120-150℃ into a thin sheet with a thickness of 1.0-2.0 mm;
[0024] S4. Lamination: The scratch-resistant transparent layer, the substrate layer and the balancing layer are stacked from top to bottom and hot-pressed at 10-20MPa pressure and 130-160℃ for 10-30 minutes. After cooling, the layers are cut to obtain the scratch-resistant stone plastic flooring.
[0025] Furthermore, in step S2, the polyvinyl chloride resin is melt-plasticized using a mixer or a twin-screw extruder, and the plasticizing temperature is controlled at 170-185℃.
[0026] Furthermore, the hot pressing and lamination in step S4 is carried out in a continuous laminator, and the cooling method is air cooling or water cooling, with a cooling rate ≤5℃ / minute.
[0027] The ultraviolet light absorber described in this invention is one of the key additives for scratch-resistant transparent layers. Its core function is to absorb ultraviolet radiation and convert it into harmless heat energy, thereby protecting the floor from the following damages: preventing molecular chain breakage in PVC materials under ultraviolet irradiation; avoiding yellowing of the material and ensuring the long-term optical performance of the scratch-resistant transparent layer; and working together with nano-silica and polysiloxane additives to enhance the weather resistance and mechanical stability of the floor. The multi-conjugated heteroaromatic rings in the molecule form an extended π-electron system, which can efficiently absorb ultraviolet light (UVA / UVB) in the 280-400nm wavelength band. The hydroxyl groups (-OH) in the structure form intramolecular hydrogen bonds with nitrogen atoms. When ultraviolet light is absorbed, the electronically excited state causes protons to transfer from the hydroxyl group to the nitrogen atom, forming a transient tautomer. The tautomer converts energy into heat energy through non-radiative relaxation, and then the protons return to the original structure. This process can be repeated, achieving continuous conversion of light energy. The alkyl chain stabilizes the molecular conformation through steric hindrance, preventing photodecomposition side reactions and enhancing compatibility with PVC materials. The ultraviolet light absorber described in this invention solves the aging problem of stone plastic flooring under ultraviolet light through a three-in-one mechanism of light absorption by multiple conjugated heteroaromatic rings, energy dissipation by proton transfer of hydroxyl groups, and stabilization of the alkyl chain structure.
[0028] The scratch-resistant stone-plastic flooring of this invention has a three-layer structure (scratch-resistant transparent layer, substrate layer, and balancing layer) and the synergistic effect of specific components therein, which solves the three major technical problems of poor wear resistance, insufficient UV resistance and weak interlayer bonding of stone-plastic flooring. Specifically, the top scratch-resistant transparent layer contains polyvinyl chloride resin as a basic skeleton to provide mechanical strength. Nano-silica with a particle size of 10-50nm forms a dense surface layer through uniform dispersion, significantly improving hardness and scratch resistance. Polysiloxane scratch-resistant additives form a low-friction coefficient lubricating film on its surface to reduce wear. Specific ultraviolet light absorbers absorb 280-400nm ultraviolet rays through intramolecular hydrogen bonding and convert them into heat energy to prevent yellowing and molecular chain breakage. The middle 1.5-5.0mm thick substrate layer is mainly composed of polyvinyl chloride resin. After being melted and plasticized at 160-190℃, it provides a supporting and buffering function and forms a molecular-level bond with the transparent layer through high-temperature hot pressing. The balancing layer uses cork material, which is densified at 120-150℃, and uses its natural elasticity to compensate for stress and prevent deformation. The synergistic effect of these three components is as follows: the enhanced hardness of nano-silica and the friction-reducing properties of polysiloxane additives work together to reduce surface wear; the ultraviolet absorber protects the polyvinyl chloride matrix from degradation through photothermal conversion mechanism, while the nanoparticles scatter residual ultraviolet rays; through hot-pressing composite under 10-20MPa pressure and controlled cooling rate, the polysiloxane in the transparent layer enhances interfacial activity, and the molten substrate layer penetrates into the cork layer to form an interlocking structure, completely solving the delamination problem; the twin-screw extrusion and continuous lamination process in the preparation process ensures uniform dispersion of components and tight bonding between layers, ultimately achieving high wear resistance, long-term resistance to ultraviolet aging, and strong overall bonding force, meeting the stringent requirements for floor durability in high-traffic areas.
[0029] Compared with the prior art, the beneficial effects of the present invention are:
[0030] 1. Significantly improves wear resistance: By using polyvinyl chloride resin as the basic skeleton, combined with nano silica and polysiloxane scratch-resistant additives, a dense and low-friction coefficient protective layer is formed on the floor surface, effectively reducing the damage caused by daily friction and scratches to the floor and extending the service life of the floor.
[0031] 2. Enhanced UV resistance: Specific UV absorbers can absorb ultraviolet rays in the 280-400nm wavelength band, preventing the molecular chain of polyvinyl chloride material from breaking under ultraviolet radiation, avoiding yellowing of the material, ensuring that the scratch-resistant transparent layer maintains its optical properties for a long time, realizing the continuous conversion of light energy, and solving the aging problem of stone plastic flooring under ultraviolet radiation.
[0032] 3. Optimized interlayer bonding: The three-layer structure and the synergistic effect of specific components form a molecular-level bond with the transparent layer through high-temperature hot pressing. The natural elasticity of cork is used to compensate for stress and prevent deformation. The twin-screw extrusion and continuous lamination process in the preparation process ensures that the components are evenly dispersed and tightly bonded between the layers, ultimately achieving high wear resistance, long-lasting anti-UV aging and strong overall bonding. Attached Figure Description
[0033] Figure 1 This is a schematic diagram of a scratch-resistant stone-plastic flooring structure according to the present invention;
[0034] 1 is a scratch-resistant transparent layer, 2 is a substrate layer, and 3 is a balancing layer.
[0035] Figure 2 The ultraviolet light absorber 1 described in this invention 1 HNMR image. Detailed Implementation
[0036] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0037] Preparation Example 1
[0038] Synthesis of UV absorber 1:
[0039]
[0040] A1 - Feeding: Under a nitrogen atmosphere, add 25g of raw material 1, 13.05g of raw material 2, 17.18g of anhydrous potassium carbonate, and 250g of a mixed solution of toluene, ethanol, and water (volume ratio 2:1:1) to the reaction system in sequence. Stir until homogeneous, purge with nitrogen twice, add 2.15g of tetra(triphenylphosphine)palladium to the reaction system, purge with nitrogen twice again, and heat to 95°C and reflux for 10 hours.
[0041] A1-Post-processing: After the reaction was completed, the mixture was filtered through a silica gel cake, and the organic phase was retained. The organic phase was evaporated to dryness under negative pressure at 50°C. The evaporated powder was added to 50g of ethyl acetate, heated to 80°C and stirred for 5h. The mixture was filtered while hot, and the organic phase was retained. The organic phase was evaporated to dryness under negative pressure at 50°C and subjected to silica gel column chromatography using a mixture of petroleum ether and ethyl acetate as the eluent. The eluted organic phase was evaporated to dryness under negative pressure at 50°C to obtain 21.77g of intermediate 1.
[0042] Intermediate 1 structural identification: MS[M+H] + :453.
[0043] A2-Feeding: Under a nitrogen atmosphere, add 21.77g of intermediate 1, 8.94g of raw material 3, 13.30g of potassium carbonate, 0.32g of palladium acetate, 0.48g of tri-tert-butylphosphine and 250g of toluene to the reaction system, stir until homogeneous, heat to 110℃, and reflux for 12h.
[0044] A2-Post-processing: After the reaction was completed, the temperature was slightly lowered, and the mixture was filtered using diatomaceous earth. The organic phase was evaporated to dryness under negative pressure at 50°C. 100g of ethanol was added to the evaporated powder, the temperature was raised to 95°C, and the mixture was stirred until dissolved. The temperature was lowered to 0°C for crystallization for 3 hours. The mixture was filtered, the filter cake was dried, and silica gel column chromatography was performed using a mixture of petroleum ether and ethyl acetate as the eluent. The organic phase obtained after elution was evaporated to dryness under negative pressure at 50°C to obtain 20.27g of UV absorber 1.
[0045] Structural identification of UV absorber 1: MS [M+H] + :541;
[0046] Structural identification of UV absorber 1: 1 HNMR Chloroform-d: δ8.70(s,1H),8.40(m,1H),7.92(dd,2H),7.64-7.52(m,4H),7.41(d,1H),7.31(dd,1H),6.92(p,1H),4.53(s,1H),4 .04(dd,1H),3.90(t,1H),3.84-3.67(m,2H),3.48(dd,1H),2.44(d,3H),1.74(s,2H),1.38-1.30(m,9H),0.93(s,3H),0.73(d,6H).
[0047] Preparation Examples 2-4
[0048] In Preparation Examples 2-4, ultraviolet absorber 2-ultraviolet absorber 4 were synthesized sequentially, following the same synthesis method as in Preparation Example 1, except that raw material 2 was replaced; the rest remained the same as in Preparation Example 1. Specific structures of raw material 2, ultraviolet absorber 2-ultraviolet absorber 4, and MS[M+H] are described. + The data is shown in Table 1.
[0049] Table 1. Structures of raw material 2, ultraviolet absorber 2-ultraviolet absorber 4, and MS[M+H] involved in preparation examples 2-4. + data.
[0050]
[0051]
[0052] Example 1
[0053] Preparation of a scratch-resistant stone-plastic flooring:
[0054] A scratch-resistant stone plastic flooring consists of a three-layer structure stacked from top to bottom, including a scratch-resistant transparent layer with a thickness of 0.1 mm, a substrate layer with a thickness of 3 mm, and a balancing layer with a thickness of 1.5 mm.
[0055] The scratch-resistant transparent layer is made of scratch-resistant transparent material; the substrate layer is made of polyvinyl chloride resin (purchased from Shanghai Titan Technology Co., Ltd., No. 011139172); and the balancing layer is made of cork (purchased from Xi'an Sandi Cork Co., Ltd., No. FD).
[0056] The scratch-resistant transparent material comprises the following components by weight: 90 parts of polyvinyl chloride (purchased from Tianjin Xiens Biochemical Technology Co., Ltd., item number P-0447182), 10 parts of nano-silica (purchased from Changsha Jingkang New Material Technology Co., Ltd., average particle size 50nm), 3 parts of polysiloxane scratch-resistant additive (selected from bis-3-methylpropenyloxypropyltetramethyldisiloxane, purchased from Pande (Shanghai) International Trading Co., Ltd.), and 1.5 parts of ultraviolet light absorber (ultraviolet light absorber 1 prepared in Preparation Example 1).
[0057] Preparation method:
[0058] S1. Preparation of scratch-resistant transparent layer: 90 parts of polyvinyl chloride resin, 10 parts of nano silica, 3 parts of polysiloxane scratch-resistant additive and 1.5 parts of ultraviolet light absorber are added to a mixer and mixed at 100°C for 10 minutes to obtain a mixture; the mixture is added to a twin-screw extruder, melt-extruded and granulated at 180°C, and cooled to room temperature to obtain a scratch-resistant transparent material; then calendered into a film with a thickness of 0.1 mm;
[0059] S2. Preparation of substrate layer: Polyvinyl chloride resin is melt-plasticized at 175℃ (using a twin-screw extruder) and calendered into a sheet with a thickness of 3.0mm;
[0060] S3. Preparation of the balancing layer: The cork raw material is hot-pressed at 135℃ into a sheet with a thickness of 1.5mm;
[0061] S4. Lamination and bonding: The scratch-resistant transparent layer, the substrate layer and the balancing layer are laminated from top to bottom and hot-pressed at 15MPa pressure and 145℃ for 20 minutes. After that, the product is air-cooled (cooling rate ≤5℃ / minute) and cut to obtain the scratch-resistant stone plastic flooring.
[0062] Examples 2-4
[0063] The preparation of a scratch-resistant stone plastic flooring is carried out by referring to the preparation method of Example 1, except that the ultraviolet light absorber is replaced sequentially with ultraviolet light absorber 2-ultraviolet light absorber 4 synthesized in Preparation Examples 2-4, and the rest is the same as in Example 1.
[0064] Comparative Example 1
[0065] The preparation of a scratch-resistant stone-plastic flooring is carried out by referring to the preparation method of Example 1, except that the ultraviolet light absorber is replaced with comparative compound 1, and the rest is the same as in Example 1.
[0066] Comparative compound 1: UV-360, an ultraviolet light absorber.
[0067] Comparative Example 2
[0068] The preparation of a scratch-resistant stone-plastic flooring is carried out by referring to the preparation method of Example 1, except that the ultraviolet light absorber is replaced with comparative compound 2, and the rest is the same as in Example 1.
[0069] Comparative compound 2:
[0070] Comparative Example 3
[0071] The preparation of a scratch-resistant stone-plastic flooring is the same as in Example 1, except that the ultraviolet light absorber is not added.
[0072] Comparative Example 4
[0073] The preparation of a scratch-resistant stone-plastic flooring is carried out by referring to the preparation method of Example 1, except that the mass fraction of nano-silica is replaced with 1 part, and the rest remains the same as in Example 1.
[0074] Comparative Example 5
[0075] The preparation of a scratch-resistant stone-plastic flooring is carried out by referring to the preparation method of Example 1, except that the mass fraction of polyvinyl chloride is replaced with 105 parts, and the rest remains the same as in Example 1.
[0076] Performance testing:
[0077] 1. Mechanical property testing: Pencil hardness was tested according to GB / T 6739-2022 standard; impact performance was tested according to GB / T 1732-2020 standard, and the data are shown in Table 2.
[0078] 2. Weathering resistance test: The test was conducted according to the conditions specified in standard GB / T 1865-2009. During the test, the parameters such as the irradiance of the xenon arc lamp, the blackboard temperature, the relative humidity, and the water spray cycle of each sample were kept consistent to simulate the changes in light, temperature, and humidity in the natural environment. The test was conducted continuously for 2000 hours. The test specimens were then removed and the color change (ΔE / %) before and after aging was measured using a colorimeter. The experimental data are shown in Table 2. Then, the tested specimens were subjected to pencil hardness testing according to standard GB / T 6739-2022 and impact performance testing according to standard GB / T 1732-2020. The data are shown in Table 2.
[0079] Table 2. Performance test data of a scratch-resistant stone-plastic flooring prepared in the examples and comparative examples.
[0080]
[0081] Examples (1-4) demonstrated excellent performance consistency across all test dimensions, including high pencil hardness, good impact resistance (no signs of cracking), minimal color change, and excellent performance retention after aging. This indicates that the combination of specific UV absorbers significantly improves the flooring's abrasion resistance, stability, and weather resistance. In contrast, Comparative Examples (1-5) showed a downward trend in several aspects: Comparative Examples 1-2, using alternative UV absorbers, exhibited reduced hardness, impact resistance, and color stability, with a significant decline in performance retention after aging; Comparative Example 3, completely lacking UV absorbers, resulted in the worst overall performance, such as weakened hardness, decreased impact resistance, and exacerbated color changes; Comparative Example 4, by reducing the nano-silica content, showed weakened hardness and impact resistance, and worsened color stability; Comparative Example 5, while slightly better than the other comparative examples due to the increased polyvinyl chloride ratio, still could not match the overall performance level of the examples. These trends illustrate the synergistic effect of the UV absorbers and formulation components of this invention, effectively ensuring the flooring's high durability and anti-aging capabilities during long-term use.
[0082] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A scratch-resistant stone-plastic flooring, characterized in that, It consists of a three-layer structure stacked from top to bottom: a scratch-resistant transparent layer (1), a substrate layer (2), and a balancing layer (3); The scratch-resistant transparent layer (1) has a thickness of 0.05-0.3 mm, the substrate layer (2) has a thickness of 1.5-5.0 mm, and the balancing layer (3) has a thickness of 1.0-2.0 mm. The scratch-resistant transparent layer (1) is composed of a scratch-resistant transparent material, which contains the following components by weight: 80-95 parts of polyvinyl chloride, 5-15 parts of nano silica, 1-5 parts of polysiloxane scratch-resistant additives, and 0.5-3 parts of ultraviolet light absorber. The ultraviolet light absorber is a compound represented by Formula 1: Formula 1; R1 is selected from: methyl, cyano, methyl cyano, acetic acid.
2. The scratch-resistant stone-plastic flooring according to claim 1, characterized in that, The particle size of the nano-silica is 10-50 nm.
3. The scratch-resistant stone-plastic flooring according to claim 1, characterized in that, The polysiloxane-based scratch-resistant additive is bis-3-methylpropenyloxypropyltetramethyldisiloxane.
4. The scratch-resistant stone-plastic flooring according to claim 1, characterized in that, The ultraviolet light absorber is any one of the compounds shown in the following structures: ; 。 5. The scratch-resistant stone-plastic flooring according to claim 1, characterized in that, The preparation method of the scratch-resistant transparent material is as follows: the polyvinyl chloride, nano silica, polysiloxane scratch-resistant additive and ultraviolet absorber are added to a mixer and mixed at 80-120℃ for 5-15 minutes to obtain a mixture; the mixture is added to a twin-screw extruder and melt-extruded at 150-200℃, granulated and cooled to room temperature to obtain the scratch-resistant transparent material.
6. The scratch-resistant stone-plastic flooring according to claim 1, characterized in that, The material of the substrate layer (2) is polyvinyl chloride resin.
7. The scratch-resistant stone-plastic flooring according to claim 1, characterized in that, The material of the balancing layer (3) is cork.
8. A method for preparing a scratch-resistant stone-plastic flooring according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Preparation of scratch-resistant transparent layer (1): A scratch-resistant transparent material is prepared according to the method described in claim 5 and calendered into a film with a thickness of 0.05-0.3 mm; S2. Preparation of substrate layer (2): Polyvinyl chloride resin is melted and plasticized at 160-190℃, and then calendered or extruded into a sheet with a thickness of 1.5-5.0mm; S3. Preparation of the balancing layer (3): The cork raw material is hot-pressed at 120-150℃ into a thin sheet with a thickness of 1.0-2.0mm; S4. Lamination and bonding: The scratch-resistant transparent layer (1), the substrate layer (2) and the balancing layer (3) are laminated from top to bottom and hot-pressed at 10-20MPa pressure and 130-160℃ for 10-30 minutes. After cooling, the layers are cut to obtain the scratch-resistant stone plastic flooring.
9. The method for preparing a scratch-resistant stone-plastic flooring according to claim 8, characterized in that, In step S2, the polyvinyl chloride resin is melt-plasticized using a mixer or a twin-screw extruder, with the plasticizing temperature controlled at 170-185℃.
10. The method for preparing a scratch-resistant stone-plastic flooring according to claim 8, characterized in that, The hot pressing and lamination in step S4 is carried out in a continuous laminator, and the cooling method is air cooling or water cooling, with a cooling rate of ≤5℃ / minute.
Citation Information
Patent Citations
Curing agent and preparation method thereof
CN104893255A
Adhesive film and optical display device including same
CN119177096A